As estratégias da pedagogia do assistencialismo em Belo Horizonte, 1930-1990: educação e caridade - Marco Antonio de Souza (1999)
This thesis analyses the pedagogic practices of three different welfare institutions that took care of poor familes and children in the city of Belo Horizonte, capital of the state of Minas Gerais, Brazil, from 1930 to 1990, period in which the laws to protect and assist them, such as Assistência e Proteção a Menores ( Decreto n. 17.943, 12.10.1927) and Estatuto da Criança e do Adolescente (lei n. 8069, 13.06.1990), were issued. Cidade Ozanam, Lar dos meninos Dom Orione, (catholic institutions) and Abrigo Jesus ( a spiritist doctrine follower) have been chosen due to their different religious and idealistic conceptual practices in spite of having in common a missionary and catchetical work wich tries to isolate and educate the poor, so that they can be kept away from loafing and promiscuity. The documental research was done on newspapers, magazines, meeting proceedings, official reports, records from the sheltered and photographs. Interviews with philanthropic leaders helped to make their practices clearer. The following authors are used for theoretical support: Michel Foucault, Giovanna Procacci, Bronislaw Geremek, Pierre Bourdieu, Catherine Rollet-Echalier, André Petitat, Roger Chartier, Gertrude Himmelfarb, Marion Aubrée e François Laplatine, Marcos Cezar Freitas, Maria Luiza Marcílo, Moisés Kuhlmann Jr., Cynthia Greive Veiga and Luciano Mendes de Faria Filho.